Developing a proactive service model of field hospital and disease screening center at the Royal Thai Army club During the COVID-19 crisis - Issarasongkhram, Mila; Satihaporn, Sukchai (Journal of Medical and Public Health Region 4, 2024)
This action research uses the PAOR cycle: P (Planning) A (Acting) O (Observing) R (Reflecting) 4 steps with objectives to developing a proactive service model of field hospital and disease screening center at the Royal Thai Army club during the COVID-19 crisis. Target groups are divided into 2 groups including 1) Group 1 is those whose duties are involved in setting up a field hospital and providing proactive services, totaling 18 people. 2) People undergoing COVID-19 screening at the field hospital and disease screening center at the club, Royal Thai Army, 2,381 people, study period Between 2 August 2021 - 4 March 2022, qualitative and quantitative data were collected. The tools used include recording forms, questionnaires and in-depth interviews. Content data were analyzed according to the 4-step PAOR cycle and descriptive statistics. The results of the study found that the proactive services of field hospitals and disease screening centers by implementing expedited measures to proactively search for infected people (active finding), outpatient treatment for COVID-19 patients with mild symptoms (Green group) “Meet, distribute, end” and providing home isolation services for COVID-19 patients combined into a complete service model (One Stop Service). This proactive service model has increased access to the health service system more quickly, reduce panic, relieve anxiety, help people feel safe in their daily lives and reduce the spread of disease in the community.